Deterioration of housing environment and mental health of asylum seekers – a multi-level analysis. (13th November 2019) - Mohsenpour, A; Biddle, L; Bozorgmehr, K
Abstract: Background: Asylum seekers arriving in Germany are assigned to a local district and an accommodation centre wherein. We developed and validated a six-item questionnaire for rapid assessment of housing deterioration and investigated its association with inhabitant mental health. Methods: Using cross-sectional data from a state-wide survey in Germany, we applied a random-effects modelling approach to estimate the exposure effect of housing deterioration on depression and general anxiety among a random sample of asylum seekers, using validated instruments (GAD2/PHQ2) for outcome variables. Housing deterioration was assessed on six items (windows/glass, walls/roof, garbage, graffiti, outside spaces, overall living environment) resulting in a deterioration score as exposure of interest. Additionally, we assessed the instrument's intra- and inter-rater reliability and internal consistency. Results: Of the 412 asylum seekers living in 58 accommodation centres, 45.7% reported symptoms of depression and 45.0% suffered general anxiety. Most centres (76.7%) were based in urban municipalities and 45.7% of inhabitants were living in an accommodation centre hosting ≥51 inhabitants. Preliminary adjusted odds ratio for accommodation centres with highest deterioration (Q 4) was 2.07 (0.67-6.40) for generalized anxiety, compared to 1.17 (0.45-3.08) for centres with lowest deterioration (Q 1). For depression, preliminary odds ratio was 1.92 (0.87-4.27) compared to 1.26 (0.63-2.50). The validation study confirmed inter-/intra-rater reliability (Brennan-Prediger coefficient: 0.81 and 0.92, respectively) and internal consistency (Crohnbach's α: 0.80). Conclusions: There are higher odds ratios for generalized anxiety disorder and depression among asylum seekers based on higher deterioration of housing environment. A questionnaire for rapid deterioration assessment and identification of accommodations needing further evaluation has been developed and successfully validated. Key messages: Deterioration of small-scale housing environment is associated with poorer mental health for asylum seekers living in accommodation centres. A highly reliable new tool has been developed for rapid assessment of deterioration status of accommodation centres and identification of those needing further evaluation.